(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article provides a scientific analysis of the key positive functions of artificial intelligence in education, while also examining risks such as the growing reliance on “quick results” in learning processes, declining reliability of assessment, and the potential weakening of critical thinking. In conclusion, it argues that the core issue is not whether to restrict or not AI use, but rather how to govern and manage its application.